The Negro in Illinois : The WPA Papers - Dolinar, Brian (Book collections on Project MUSE., 2013)
A major document of African American participation in the struggles of the Depression, this book was produced by a special division of the Illinois Writers' Project, one of President Roosevelt's Works Progress Administration programs.